Local leadership in public health: the role of the medical officer of health in Britain, 1872–1974 - Gorsky, Martin (BMJ Group, 2007)
The recent policy focus in British public health on the importance of local action invites consideration of historical precedent. The role and achievements of the medical officer of health (MOH), the local government official charged with public health responsibilities, is discussed. The gradual accretion of duties is traced in the first section: the mid‐Victorian concern with urban sanitation; the preventive strategies adopted after the bacteriological revolution; the extension of personal health services in the early 20th century; and the more diminished role under the National Health Service (NHS), when infectious diseases retreated. The historical verdicts passed on the MOsH are reviewed in the second section. The leading role of the MOsH in the late 19th‐century mortality decline has been reasserted, and although there is some justification in the argument that in the 20th century public health lost its focus, it is important to recall that the extension of personal health services under MOH direction signified a major extension of access to care. Similarly, the charge that MOsH did not redefine their role in the period before their final demise in 1974 is not entirely justified. The emphasis of the NHS on curative rather than preventive medicine, and the economic constraints on local authority health service expansion limited their room for manoeuvre. The history of local leadership in public health may offer some enduring lessons. These include the importance of monitoring local population health, acting as a public interface between medicine and the community, facilitating joined‐up working and confronting vested interests.